2009
DOI: 10.1111/j.1365-2966.2009.15878.x
|View full text |Cite
|
Sign up to set email alerts
|

The diversity and similarity of simulated cold dark matter haloes

Abstract: We study the mass, velocity dispersion and anisotropy profiles of Λ cold dark matter (ΛCDM) haloes using a suite of N‐body simulations of unprecedented numerical resolution. The Aquarius Project follows the formation of six different galaxy‐sized haloes simulated several times at varying numerical resolution, allowing numerical convergence to be assessed directly. The highest resolution simulation represents a single dark matter halo using 4.4 billion particles, of which 1.1 billion end up within the virial ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

77
772
3
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 781 publications
(860 citation statements)
references
References 44 publications
77
772
3
8
Order By: Relevance
“…See Diemand & Moore (2011) for a review of cusp structure. CDM simulation papers widely agree that CDM halos are expected to have cuspy centers rather than isothermal-like cores (e. g., Moore et al 1998Moore et al , 2001Klypin et al 2001Klypin et al , 2011Navarro et al 2004Navarro et al , 2010Colín et al 2004;Hayashi et al 2004;Diemand et al 2005Diemand et al , 2008Klypin, TrujilloGomez, & Primack 2011).…”
Section: Our Assumptionsmentioning
confidence: 99%
“…See Diemand & Moore (2011) for a review of cusp structure. CDM simulation papers widely agree that CDM halos are expected to have cuspy centers rather than isothermal-like cores (e. g., Moore et al 1998Moore et al , 2001Klypin et al 2001Klypin et al , 2011Navarro et al 2004Navarro et al , 2010Colín et al 2004;Hayashi et al 2004;Diemand et al 2005Diemand et al , 2008Klypin, TrujilloGomez, & Primack 2011).…”
Section: Our Assumptionsmentioning
confidence: 99%
“…This dependence is less pronounced for the decaying DM, since J dec ∝ ρ. Motivated by the numerical simulations, we model the DM density distribution assuming the Einasto profile [42], with scale radius r s = 0.15 kpc, scale density ρ s = 1.1×10 8 M ⊙ kpc −3 and slope α = 0.30 [19,43].…”
Section: The Astrophysical Factor J For Seguementioning
confidence: 99%
“…Navarro, Frenk & White (1996) showed that simulated dark halos have a universal internal density distribution, now known as the NFW profile. Although there have been some revisions, the general form has remained, and the inner regions of simulated dark halos are found to be cusped with logarithmic slopes in the range −1.2 to −0.75 (Navarro et al 2010). CDM simulations have also revealed the existence of a universal spin distribution and of relations between the characteristic parameters of a ⋆ E-mail:breddels@astro.rug.nl dark halo such as concentration and mass (e.g Bullock et al 2001).…”
Section: Introductionmentioning
confidence: 99%